The Three Approaches Required for the Study of Social Sciences - Silva, Felipe Rosa da (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
Logical positivism is invalid for the study of social sciences. Therefore, it is necessary to use a valid methodology. It consists of studying together three necessary approaches to a same human reality: theoretical, historical-interpretative and ethical. Besides, this methodology addresses the issue of the genesis of ethics, the dichotomy between the thoughts of Hayek and Rothbard: evolutionary ethics derived from history or universal ethics built from the axiom of action. Working, separating and listing those three approaches: that is the complete methodology to be used in the study of social sciences.